Transcriptomic analysis of de novo folate biosynthetic genes in Lactobacillus plantarum strain 4_3 in fermented soybean. Issue 5 (10th April 2019) - Liu, Chen-Jian; Wu, Bian; Zhang, Si-Yao; Li, Qiang-Kun; Zeng, Xue-Qin; Yang, En; Luo, Yi-Yong; Li, Xiao-Ran
Abstract : Folate is an important intermediate in cellular metabolism. Abstract : Folate is an important intermediate in cellular metabolism. However, because of a lack of key enzymes in the folate biosynthetic pathway, humans require supplementation with dietary folate. Some Lactobacillus plantarum strains have the ability to produce folate. To gain a better understanding of the folate biosynthetic pathway in the L. plantarum strain 4_3, which generates high folate yields, L. plantarum strain 4_3 was grown in folic acid casei medium (FACM) and fermented soybean, after obtaining a draft genome sequence. The pH values and folate yields were monitored during culturing, as were the transcriptomic profiles of cultured bacteria. The folate content increased for 12 h and then decreased before increasing again. All the genes involved in the de novo biosynthesis of folate were detected in both the genomic and transcriptomic data. The upregulation of the para -aminobenzoate biosynthesis pathway could explain the folate production in fermented soybean. Soybeans are a good substrate for the production of functional foods because of their well-suited cultivation and nutritional quality. The results of this study provide a good explanation for the high folate production observed during the fermentation of soybeans.